Geographical analysis of the effect of electronic games on the low level of primary education for boys in the city of Kut. - البدري م.د.وسام عبد الحسن (lark, 2020)
Electronic games are a major part of the life of young pupils, as they work to provide the side of amusement and entertainment, but when they are at the expense of the academic side, it represents a major problem whose impact is reflected on the success levels of pupils, as the research aims to study the causes of low levels of success and analyze the economic, social and geographical factors And its impact on families who suffer from the low results of their children and show the role of electronic games practiced by male pupils for the elementary stage on the increasing failure rates starting from the type of devices used and the availability of the Internet and the time taken By playing to find out the true extent of the problem, to clarify the effects and damages resulting from that, and to develop appropriate solutions